Propuesta de un archivo virtual dinámico en PHP para gestionar la documentación electoral manuscrita del Archivo Histórico del Congreso de los Diputados de España - Villarejo Sánchez, Nadia (Documentación de las Ciencias de la Información, 2007)
The programming language PHP is a mixture of different programming languages. Mainly, it uses the syntax that most of the programmers knows of the programming language C, but is very different from this last one, since PHP is an interpreted programming language and serves like computer science resource to solve to problems of diffusion and archive document conservation. For that reason, appears in this article the graphical interface of a model possible of virtual archive in programming language PHP, that it can serve to conserve and to diffuse the handwritten electoral documentation of the Historical Archive of the Congress of the Deputies of Spain. In order to show the characteristics of the virtual archive working like historical information system, has been selected a concrete documentary sample; the electoral handwritten documentation pertaining to D. Práxedes Mateo Sagasta and Escolar (1854-1901); documents deteriorated, whose index of legibility –in some cases– it is confused because the inks has transfered by reverse of the paper format, therefore it is demonstrated the functioning of search tools and recovery of the concrete virtual archive and the presentation of electoral documents in digital format.